2023
DOI: 10.3390/cancers15051490
|View full text |Cite
|
Sign up to set email alerts
|

Management and Oncologic Outcomes of Close and Positive Margins after Transoral CO2 Laser Microsurgery for Early Glottic Carcinoma

Abstract: Background: The present study analyzed the impact of margin status on local control and survival, and the management of close/positive margins after transoral CO2 laser microsurgery for early glottic carcinoma. Methods: 351 patients (328 males, 23 females, mean age 65.6 years) underwent surgery. We identified the following margin statuses: negative, close superficial (CS), close deep (CD), positive single superficial (SS), positive multiple superficial (MS), and positive deep (DEEP). Results: A total of 286 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…These findings build upon previous literature evaluating the prognostic effect of margin positivity for early stage LSCC treated with endoscopic surgery. Previous studies have found rates of margin positivity for these tumors to be between 12.0% and 45.4%, 3–12 similar to the margin positivity rate of 23.6% in the present study. In addition, this study's findings of 68.2% 5‐year overall survival for patients with positive margins and 77.0% for patients with negative margins are similar to previous studies, which found overall survival to be between 67.1% and 89.0% for patients with positive margins and 82.9% and 96.8% for patients with negative margins 3,6,9 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These findings build upon previous literature evaluating the prognostic effect of margin positivity for early stage LSCC treated with endoscopic surgery. Previous studies have found rates of margin positivity for these tumors to be between 12.0% and 45.4%, 3–12 similar to the margin positivity rate of 23.6% in the present study. In addition, this study's findings of 68.2% 5‐year overall survival for patients with positive margins and 77.0% for patients with negative margins are similar to previous studies, which found overall survival to be between 67.1% and 89.0% for patients with positive margins and 82.9% and 96.8% for patients with negative margins 3,6,9 .…”
Section: Discussionsupporting
confidence: 90%
“…Achieving negative pathologic surgical margins is believed to be an important consideration to reduce both the necessity for additional treatments, such as adjuvant treatment and re‐operation, and the risk of recurrence 2 . For Stage I‐II glottic LSCC treated with transoral laser microsurgery, surgical margin positivity rates have been reported to be between 12.0% and 45.4% 3–12 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations